Hubungan Karakteristik dan Tingkat Pengetahuan Ibu dengan Status Gizi di Posyandu Tanjung 5 Desa Sukamakmur Kecamatan Telukjambe Timur Karawang Jawa Barat (Jurnal Antara Kebidanan, 2020)
Background Children's nutritional status is one of the determinants of the quality human resources (HR), so that children who have good nutritional status are an asset and investment in human resources (HR) in the future, but on the hand, children who have poor nutritional status are a problem for human resources in the future. coming. The mother's characteristics and level of knowledge are on of the factors that can influence the nutritional status of toddlers.Objectives To determine the relationship between maternal characteristics and knowledge and the nutritional status of toddlers at Posyandu Tanjung 5, East Telukjambe District Karawang West Java. Method The research design used in this research is correlation analytic with a cross-sectional approach. In this study, the samples were all toddlers recorded at the Tanjung 5 Posyandu, Sukamakmur Village, East Telukjambe District, Karawang West Java. The sampling technique used in this research was purposive sampling with total sampling located at Posyandu Tanjung 5 Sukamakmur Village East Telukjambe District Karawang West Java. Results Univariate analysis in this study was carried out to identify the nutritional status of toddlers, age, highest level of education, employment status and mother's knowledge which was presented in the form of a frequency distribution table. Bivariate analysis in this research aims to determine the relationship between the independent variable and the dependent variable.Conclusions There is a relationship between characteristics in the category of maternal education and maternal knowledge with the nutritional status of toddlers.